Revisionary study on European species of the Empria candidata complex (Hymenoptera, Symphyta, Tenthredinidae) - Macek, Jan; Kula, Emanuel (Zootaxa, 2015)
Two species of the Empria candidata species complex, E. candidata (Fallén, 1808) and E. magnicornis (Eversmann, 1864) spec. rev., comb. nov., are revised and redescribed. The males and larvae of both species are identified, described and the males are associated with the corresponding females. The species are redefined based on the revision of the available types. Lectotypes are designated for Tenthredo (Allantus) repanda Klug, 1816 and Tenthredo (Macrophya) magnicornis Eversmann, 1864.